A Mathematical Model of in-Host Tuberculous Granuloma (Journal of Nonlinear Modeling and Analysis, 2024)
Tuberculosis is the second biggest infectious disease killer aftercoronavirus. In this paper, we analyze a mathematical model of in-host tuberculous granuloma, obtaining the basic reproduction number, as well as theexistence and stability of equilibrium points. The sensitivity analysis providesparameters that have a significant effect on model dynamics. Finally, changesin the number of immune cells, infected macrophages and Mycobacterium tuberculosis are analyzed by numerical simulation of three disease states: clearance, latent infection and active tuberculosis. The results suggest that theimmune mechanism determing whether an infected individual will suffer fromactive or latent tuberculosis is the ability of activated infected macrophagesto kill Mycobacterium tuberculosis.
Keywords: Tuberculous granuloma; immune cell; the sensitivity analysis; stability.